Upaya Membangun Kinerja Tinggi Anggota Organisasi Melalui Motivasi Kerja - Syarifa, Lailatus; Ifadatut Thausiyah; Mansur Faliki; Olivia Kartika Putri; Mu'alimin (Idarotuna : Journal of Administrative Science, 2024)
One of the most important factors in raising organizational members' performance is their motivation at work. The desire to finish a task or activity as well one can in order to maximize work performance is known as motivation (performance). The qualitative method a kind of literature study was used to conduct this research, which involved gathering information from multiple library sources. The purpose of this study is to quantify the degree to which employee performance is enhanced in various firms by motivation. According to the research's findings, 1) work motivation is defined as a state that attempts to motivate an individual to be more excited about their work and to satisfy their desired needs in life. Employee performance, on the other hand, is the outcome of an employee's process of carrying out his or her responsibilities. (2) A manager can use a variety of strategies to increase employee performance through work motivation, including evaluating attitudes, managing well, enhancing member communication, and fostering a culture where it is difficult for a manager to place blame on subordinates. (3) Work motivation plays a critical part in the relationship between organizational members' performance and work motivation because it can motivate employees to perform their jobs to the best of their abilities and to produce positive outcomes for the company.